2021
DOI: 10.3390/brainsci11030362
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Processing and Quality of Sleep in Autism Spectrum Disorders

Abstract: Individuals with autism spectrum disorders (ASDs) commonly experience problems with the processing of tactile stimuli and poor quality of sleep. The aim of the present study was to analyze whether tactile stimuli modulation (TSM) disorders might be linked to insomnia prevalence in ASD individuals. We hypothesized that sleep disorders in children with ASD may result from improper tactile under/over responsivity. The study included 27 children diagnosed with ASD, aged 6.8 (±2.9 years) with male dominance (n = 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Other investigators indicated that the combination of sleep concerns and sensory reactivity differences in autistic children exceeded that found in neurotypical children ( Nieminen-von Wendt et al, 2005 ; Reynolds et al, 2012 ; Tzischinsky et al, 2018 ; Wang et al, 2019 ; Eyuboglu and Eyuboglu, 2020 ) and that a greater number of sensory integration/processing differences could be seen in autistic children with sleep concerns ( Klintwall et al, 2011 ). Jamioł-Milc et al (2021) , investigating tactile modulation differences in autistic children through parent interview and observation, identified a potential relationship between tactile hypo-responsivity and insomnia but no relation between tactile hyper-responsivity or sensory seeking and insomnia. Interestingly, Ghanbari and Rezaei (2016) found no relationship between sensory processing differences and sleep concerns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators indicated that the combination of sleep concerns and sensory reactivity differences in autistic children exceeded that found in neurotypical children ( Nieminen-von Wendt et al, 2005 ; Reynolds et al, 2012 ; Tzischinsky et al, 2018 ; Wang et al, 2019 ; Eyuboglu and Eyuboglu, 2020 ) and that a greater number of sensory integration/processing differences could be seen in autistic children with sleep concerns ( Klintwall et al, 2011 ). Jamioł-Milc et al (2021) , investigating tactile modulation differences in autistic children through parent interview and observation, identified a potential relationship between tactile hypo-responsivity and insomnia but no relation between tactile hyper-responsivity or sensory seeking and insomnia. Interestingly, Ghanbari and Rezaei (2016) found no relationship between sensory processing differences and sleep concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Looking within specific sensory systems, Tzischinsky et al (2018) used the Hebrew version of the SP ( Neuman et al, 2004 ) and found that while tactile and oral sensitivity differences were related to total sleep disturbances [Hebrew CSHQ (45)], tactile hyper-reactivity explained 24% of the variance in total sleep disturbance scores in autistic children. Jamioł-Milc et al (2021) investigated tactile modulation disorders (either hyper- or hypo-reactivity) and poor-quality sleep in autistic children using their own tools. While they did not find significant relationships because of small sample size, they suggested that insomnia in autistic children could be related to tactile hypo-reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use of relaxing music, aromatherapy, minimizing bright lights or the use of specific lighting to restore normal circadian rhythms, the avoidance of particular foods or stimulants, and tactile input such as from massage or weighted blankets (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). It is noteworthy that individuals with autism, elderly nursing home residents, and dementia patients all appear to be disproportionately affected by sleep disorders and seem to respond to sensory stimulation (39)(40)(41)(42)(43). Based on these findings, we hypothesized that tactile PSS might be beneficial in improving sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Grossi et al [25] attempted to classify different RRB patterns after video-recording a group of autistic individuals within a naturalistic context. Third, Jamioł-Milc et al [26] investigated the relationship between tactile stimuli and quality of sleep in ASD. Fourth, Kadlaskar et al [27] compared different aspects of tactile cues between autistic and typically developing children, further underlying the importance of research on sensory processing in this population.…”
mentioning
confidence: 99%